Lycium barbarum Polysaccharides Attenuate Cisplatin-Induced Hair Cell Loss in Rat Cochlear Organotypic Cultures - Liu, Quan (Molecular Diversity Preservation International (MDPI), 2011)
The aim of the present study was to investigate the effects of Lycium barbarum polysaccharides (LBP) on cisplatin-induced hair cell damage in the organ of Corti explant. The neonatal (P2–3) rat organ of Corti explant was exposed to cisplatin (20 μM; 48 h) with or without LBP pretreatment (150 and 600 μg/mL; 24 h). Hair cell loss was indicated by FITC-labeled phalloidin staining. The level of reactive oxygen species (ROS) and alteration of mitochondrial membrane potential (ΔΨ(m)) in hair cells were analyzed using fluorescent probes 2′,7′-dichlorofluorescein diacetate and JC-1, respectively. The results showed that LBP significantly attenuated hair cell loss (p < 0.01). Hair cells pretreated with LBP showed significant reduction in ROS production and the decline of ΔΨ(m) compared with cisplatin alone group (p < 0.01), indicating the protective effect of LBP on cisplatin-induced hair cell loss. Taken together, these results indicate that LBP was effective in attenuating cisplatin-induced hair cell loss by reducing the production of ROS and maintaining mitochondrial ΔΨ(m).